Loss of oncogenic ras expression does not correlate with loss of tumorigenicity in human cells. - Plattner, R (1996)
ras oncogenes are mutated in at variety of human tumors, which suggests that they play an important role in human carcinogenesis. To determine whether continued oncogenic ras expression is necessary to maintain the malignant phenotype, we studied the human fibrosarcoma cell line, HT1080, which contains one mutated and one wild-type N-ras allele. We isolated a variant of this cell line that no longer contained the mutated copy of the N-ras gene. Loss of mutant N-ras resulted in cells that displayed a less transformed phenotype characterized by a flat morphology, decreased growth rate, organized actin stress fibers, and loss of anchorage-independent growth. The transformed phenotype was restored following reintroduction of mutant N-ras. Although loss of the oncogenic N-ras drastically affected in vitro growth parameters, the variant remained tumorigenic in nude mice indicating that mutated N-ras expression is not necessary for maintenance of the tumorigenic phenotype. We confirmed this latter observation in colon carcinoma cell lines that have lost activated K-ras expression via targeted knockout of the mutant K-ras gene.